2022
DOI: 10.3389/fmars.2022.984219
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale foraging segregation in a green turtle (Chelonia mydas) feeding ground in the Bijagós archipelago, Guinea Bissau

Abstract: Green turtles (Chelonia mydas) are highly dependent on neritic foraging areas throughout much of their life. Still, knowledge of recruitment dynamics, foraging habits, and habitat use in these areas is limited. Here, we evaluated how the distribution and food preferences of green sea turtles from different life stages varied within a foraging aggregation. We focused on two islands in Guinea-Bissau, Unhocomo and Unhocomozinho, using water captures and survey dives to record habitat use and characteristics, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…It is also important to note that the current study analyzed juvenile green turtles that were stranded on the beach. Consequently, it was not possible to investigate a wide size-range, which could have interfered in the detection of a possible change in foraging niche among turtles, as found by Madeira et al (2022) for green turtles sampled over a wide size-range in a feeding area in the Bijagoś archipelago, in Guinea Bissau, for example.…”
Section: Juvenile Green Turtlesmentioning
confidence: 99%
“…It is also important to note that the current study analyzed juvenile green turtles that were stranded on the beach. Consequently, it was not possible to investigate a wide size-range, which could have interfered in the detection of a possible change in foraging niche among turtles, as found by Madeira et al (2022) for green turtles sampled over a wide size-range in a feeding area in the Bijagoś archipelago, in Guinea Bissau, for example.…”
Section: Juvenile Green Turtlesmentioning
confidence: 99%
“…Guinea-Bissau hosts a major green turtle population, with most of the nesting concentrated in the southeast of the Bijagós archipelago, and foraging grounds spreading through this archipelago [ 33 ], with an important one around the westernmost islands [ 34 ]. Two recent studies found that juvenile green sea turtles in this foraging ground feed mostly on red algae [ 35 , 36 ], thus, it is likely that red algae microbiomes are present in the GI tract of these turtles. Species of red algae, such as Laurencia dendroidea , Spyridia filamentosa and the corallinaceae, Jania sp., are known to be part of the local benthic macrophyte composition of the Bijagós archipelago in Guinea-Bissau [ 35 ].…”
Section: Introductionmentioning
confidence: 99%